Calculation of costs of pregnancy-and puerperium-related care: Experience from a hospital in a low-income country - Sarowar, M.G.; Medin, E.; Gazi, R.; Koehlmoos, T.P.; Rehnberg, C.; Saifi, R.; Bhuiya, A.; Khan, J. (I C D D R B - Centre Health Population Research, 2010)
Calculation of costs of different medical and surgical services has numerous uses, which include monitoring the performance of service-delivery, setting the efficiency target, benchmarking of services across all sectors, considering investment decisions, commissioning to meet health needs, and negotiating revised levels of funding. The role of private-sector healthcare facilities has been increasing rapidly over the last decade. Despite the overall improvement in the public and private healthcare sectors in Bangladesh, lack of price benchmarking leads to patients facing unexplained price discrimination when receiving healthcare services. The aim of the study was to calculate the hospital-care cost of disease-specific cases, specifically pregnancy-and puerperium-related cases, and to indentify the practical challenges of conducting costing studies in the hospital setting in Bangladesh. A combination of micro-costing and step-down cost allocation was used for collecting information on the cost items and, ultimately, for calculating the unit cost for each diagnostic case. Data were collected from the hospital records of 162 patients having 11 different clinical diagnoses. Caesarean section due to maternal and foetal complications was the most expensive type of case whereas the length of stay due to complications was the major driver of cost. Some constraints in keeping hospital medical records and accounting practices were observed. Despite these constraints, the findings of the study indicate that it is feasible to carry out a large-scale study to further explore the costs of different hospital-care services.